Polish rural sociology - Kaleta, Andrzej (Sociology of rural worlds in Poland and France: field research and studies, 2024)
The development of Polish rural sociology was determined by breakthrough events in the 20th century history of Poland: regaining independence (1918), the end of the II World War resulting in the establishment of communist Poland (1945) and its dismantling under the influence of the Solidarity social movement (1980‒1989). The indicated historical events define three stages of development of Polish rural sociology. In the first one, i.e. institutionalization (1918‒1939), the first academic and government research centers were established and the theoretical and methodological foundations of the discipline were proposed. The second period, i.e. the socialist modernization of rural areas (1945‒1989), was characterized by subordination of the discipline to the political doctrine and imposition of focal points, including the countryside and agriculture, subjected to intensive processes of socialist industrialization of agriculture and urbanization of rural areas. The political and socio-economic reforms initiated in the late 1980s introduced Polish rural sociology into the third phase of development, called the period of searching for a new paradigm. The countryside and agriculture entered the phase of changes, defined as the processes of adaptation of the countryside and agriculture to the conditions of development of capitalist society, which rural sociology tried to theoretically justify, pointing to their not always positive practical consequences.